Etude expérimentale d'un humidificateur d'air utilisée pour le refroidissement d'un poulailler - Ad, Abdelkamel; Gasmi, Miloud; Bellamouchi, Mohammed Yacine (université d'eloued, 2023)
"This thesis focuses on the experimental study of an air humidifier prototype used to cool a poultry house located in arid areas in Algeria (El-Oued). The prototype's design is based on insulating walls, such as sandwich panels. The humidification system consists of a porous exchange body (filling) that allows fresh air from the outside to enter and a special fan that draws air from the inside and expels it outside. We used three local materials for the exchange body (filling), such as palm fiber, palm leaves, and stipa plants. After a series of measurements conducted from 1:00 PM to 3:00 PM in the afternoon, we found that the palm fiber-based filling provided the best performance. This technique improves the air quality throughout the poultry house, resulting in increased production while minimizing energy costs." "ھذه المذكرة تتناول الدراسة التجریبیة لنموذج أولي لمرطب الھواء المستخدم لتبرید حظیرة تربیة الدواجن الموجودة في المناطق القاحلة في الجزائر (الوادي). یستند تصمیم ھذا النموذج إلى جدران عازلة مثل الألواح الشطیرة. یتكون نظام الترطیب من ھیكل تبادل مسامي (حشوة) یسمح بدخول الھواء النقي من الخارج إلى الداخل، بالإضافة إلى مروحة خاصة تسحب الھواء من الداخل وتطرحها إلى الخارج . لقد استخدمنا ثلاثة مواد محلیة لھیكل التبادل (الحشوة) مثل ألیاف النخیل وأوراق النخیل ونبات الحلفاء. بعد سلسلة من القیاسات التي تم إجراؤھا من الساعة 00:1 ً ظھرا حتى الساعة 00:3 ً عصرا، لاحظنا أن حشوة ألیاف النخیل توفر أفضل أداء. تسمح ھذه التقنیة بتحسین جودة الھواء في حظیرة الدواجن، مما یؤدي ذلك إلى زیادة الإنتاج مع تقلیل تكالیف الطاقة . "
مذكرات ماستر تخصص طاقات متجددة
Keywords: air humidifier, poultry, cooling, energy efficiency.; مرطب الھواء، الدواجن، التبرید، الكفاءة الطاقویة